Eksplorasi Tumbuhan Beracun Di Cagar Alam Dolok Tinggi Raja Kabupaten Simalungun Sumatera Utara - Vivien Christon Manalu; Yunus Afifuddin; Lamek Marpaung (Program studi Kehutanan USU, 2015)
Research about Exploration of Poisonous Plants at Dolok Tinggi Raja Nature Preserve did analysis identification, secondary metabolit and potential development of the aspect local knowledge with survey local knowledge. The second were aspect biodiversity with analysis of vegetation data collection. And the third were aspect phytochemical with detect the contain of secondary metabolit. The exploration of poisonous plant in Dolok Tinggi Raja Nature Preserve found 11 kinds of toxic plants. The result of this research shows that five kinds of toxic plants which has a greater chance that cultivated as asource of biopesticide is Hati Lando (Deccana pubescens Roth.), Hawe Bolanda (Colocasia esculenta (L.) Schott.), Langge (Homalonema propinqua Ridl.), Lappisi (Calamus erectus Roxb.), Latong Andosarih (Urtica dioca L.), Latong Anduri (Litsea leefeana), Latong Barat (Urtica cannabina L.), Osang-osang Balua (Caladium lindenii Madison.), Silam-lam Bau (Clidemia hirta Bl.), Tabar-tabar (Costus speciosus Sm.) and Tubung (Litsea albicans (Kurz) Hook.f.). Keywords : Poisonous plant, Dolok Tinggi Raja Nature Preserved, Phytochemical, Biopesticide